Postoperative HbA1c Level as a Predictor of Rotator Cuff Integrity After Arthroscopic Rotator Cuff Repair in Patients With Type 2 Diabetes. Issue 2 (16th February 2023) - Yeom, Ji Woong; Kholinne, Erica; Kim, Dong Min; Lee, Jun-Bum; Hui, Ben; AlAhmadi, Basim Masoud; Shin, Myung Jin; Kim, Minsoo; Park, Jeong Hee; Koh, Kyoung-Hwan; Jeon, In-Ho
Background: In patients with type 2 diabetes mellitus (DM), preoperative glycosylated hemoglobin (HbA1c) is associated with outcomes after arthroscopic rotator cuff repair (ARCR); however, the relationship between outcomes and postoperative serum glycosylated hemoglobin (HbA1c) after ARCR has not been investigated. Purpose: To evaluate outcomes after ARCR in patients (1) with and without DM and (2) with DM according to their pre- and postoperative HbA1c levels. Study Design: Cohort study; Level of evidence, 3. Method: Included in this study were 148 patients without DM and 35 patients with type 2 DM who underwent ARCR between January 1, 2017, and December 31, 2019. Clinical and radiological outcomes were evaluated preoperatively and at the latest clinical follow-up. Postoperative magnetic resonance imaging was performed after 12 months. In patients with type 2 DM, HbA1c levels were evaluated preoperatively as well as 6 and 12 months postoperatively; patients with an HbA1c level of ≥7% were defined as having uncontrolled DM. Multivariate logistic regression analyses were performed to determine the factors for retears after ARCR. Results: The retear rates after ARCR were 22.9% (8/35) and 16.9% (25/148) in patients with and without DM, respectively. The retear rates were significantly higher in the 6-month postoperative uncontrolled DM group than in the controlled DM and non-DM groups (50% vs 8.7% and 16.8%; P < .05). The odds ratio for retears in the postoperative uncontrolled DM group was 5.555 ( P =0.01) compared with the non-DM group. Among the patients with DM, in the uncontrolled DM group, 6-month postoperative hyperglycemia was superior in accuracy, sensitivity, and specificity for predicting retears after ARCR than preoperative hyperglycemia (77.1% vs 62.9%, 75% vs 37.5%, and 77.8% vs 70.4%, respectively). Conclusion: This study demonstrated the association between uncontrolled postoperative DM and an increased risk of retears compared with no DM or controlled DM. Furthermore, postoperative HbA1c values were correlated more closely with the risk of retears than preoperative HbA1c values.